The Problem of Dynamic Process Manifestation in Identification of Organic Compounds by NMR Spectroscopy - N. E. Kuz’mina; S. V. Moiseev; A. I Luttseva (Регуляторные исследования и экспертиза лекарственных средств, 2020)
The number, shape and position of NMR spectral lines depend on dynamic processes, and this creates certain difficulties in identification of pharmaceutical substances by NMR spectroscopy. The aim of the paper was to study instances of manifestation of intramolecular dynamic processes that affect identification of organic compounds by NMR, and to illustrate the potential of the methods used for their reduction, as well as associated problems.Materials and methods: 1H and 13C spectra of the following pharmaceutical substances: «buserelin acetate», «valsartan», «goserelin acetate», «iopromide», «clopidogrel hydrogensulfate», «omeprazole», «proroxan», «risperidone», «triptorelin acetate», and «enalapril maleate» were used to demonstrate negative effects of dynamic processes. The spatial structures of conformers were established by 1H-1H ROESY experiments. The quantum-chemical calculation of geometric and thermodynamic characteristics of different conformers was carried out by the PM3 method, and electronic characteristics—by the AM1 method with the help of the HyperChem software.Results: the authors analysed intramolecular dynamic processes which are most commonly encountered in expert work: pyramidal inversion of nitrogen in a heterocyclic compound (risperidone, proroxan, clopidogrel), rotation of molecular fragments around the amide bond (valsartan, iopromide, enalapril), prototropic rearrangements (buserelin, goserelin, omeprazole, triptorelin). The change in exchange rates was explained from the perspective of the change in the system of intra- and intermolecular nonvalent interactions.Conclusions: the use of traditional methods for increasing the rate of dynamic processes (increasing the temperature and changing the solvent) does not always eliminate the negative effects of intramolecular transformations. Methods of smoothing the spectral manifestations of dynamic processes have limited application due to strong intramolecular nonvalent interactions which prevent the conversion of the dynamic process rate into fast exchange. Experts and manufacturers should take into account the manifestation of dynamic processes during identification of pharmaceutical substances by NMR spectroscopy.